﻿New species of Plesioaxymyia Sinclair (Diptera, Axymyiidae) from the Palaearctic Region, including an updated molecular phylogeny of the family - Polevoi, Alexei; Burdíková, Nikola; Ševčík, Jan (ZooKeys, 2025)
The family Axymyiidae includes four extant genera and nine species known from the Holarctic and Oriental regions, with only one species Mesaxymyiakerteszi (Duda, 1930) occurring in Europe. The genus Plesioaxymyia Sinclair, 2013 was first discovered in Alaska in 1962, but officially described only many years later. Up to now, the genus included one species Plesioaxymyiavespertina Sinclair, 2013, known from two female specimens from western North America. During the study of the Diptera fauna in Paanajarvi National Park (Northwest Russia), one female specimen of Plesioaxymyia, was found. It differs from the Nearctic P.vespertina by details of its female terminalia and is recognized as a new species, herein described as Plesioaxymyiaimprevista sp. nov. The biology and geographic distribution of Plesioaxymyia is briefly discussed. The phylogenetic position of the genus, along with the family Axymyiidae is analyzed in the light of new molecular data, including sequences of three mitochondrial (ribosomal 12S and 16S and protein-encoding COI) and three nuclear genes (ribosomal 18S and 28S, protein-encoding CAD) for 72 terminal taxa. Axymyiidae is recovered as a monophyletic group with closest relatives in the infraorder Culicomorpha and Plesioaxymyiaimprevista sp. nov. representing the sister taxon to all the other species of Axymyiidae included in the analysis.
Keywords: Russia; Nematocera; distribution; Biology; new species; lower Diptera; systematics